Cytokine Production by a Human Endothelial Cellline in Response to Candida Albicans - Lim, Pei Ching (2005)
Candida albicans is the most common aetiological agent that causes haematogenously disseminated candidiasis. Under conditions that compromise the host immune system, C. albicans disseminates from mucosal sites and results in a progressive disease associated with high rates of mortality. Cytokines are important immunomodulators in coordinating the host defense against C. albicans infection. Human endothelial cells are known to produce various types of cytokines in response to pathogen invasion. The present study was undertaken to identify the cytokines that are involved in the host defense against C. albicans, as well as, to determine the importance of direct cell-to-cell contact in triggering expression of cytokines. In addition, the involvement of Toll-like receptor (TLR)2, TLR4 and nuclear factor-& (NF-KB) in the host defense against C. albicans were also examined. Expression of cytokines by endothelial cells in response to C. albicans was investigated by using an in vitro model of human umbilical vein endothelial cell line (HUVEC) co-cultured with Candida spp. Both conventional and real time PCR showed that among the cytokines studied, only granulocyte-macrophage colony-stimulating factor (GM-CSF) was found to be differentially expressed in HUVEC upon stimulation with C. albicans. Elevated levels of GM-CSF were found in the co-culture of HUVEC with C. albicans but not in the other non-albicans Candida spp. Three additional C. albicans strains co-cultured with HUVEC also showed a similar pattern of increased GM-CSF expression, although at different levels from strain to strain. This provided evidence that the induction of GM-CSF was not confined to only a particular clinical strain of C. albicans. On the other hand, C. dubliniensis, which possessed a similar phenotype as C. albicans failed to stimulate a similar pattern of GMCSF expression in HUVEC. The induction of GM-CSF was then found to be contactdependent via the use of cell culture insert to physically separate C. albicans from adhering to the HUVEC monolayer. Pretreatment with anti-TLR2 and anti-TLR4 antibodies showed that TLR4 but not TLR2 was involved in the induction of GM-CSF expression by HUVEC. In addition, pretreatment with SN50 inhibitor also demonstrated that NF-KB may be involved in stimulating expression of GM-CSF transcript. In conclusion, we have discovered that HUVEC is involved in the innate immune response to C. albicans by producing GM-CSF cytokine through the activation of TLR4 and also NF-KB transcription factor in a contact-dependent manner.